Políticas públicas de habitação antagônicos às moradias (im)próprias na cidade Manaus/AM - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
This research was carried out in the city of Manaus, capital of the State of Amazonas, in the Midwest area, in the Nova Esperança neighborhood, in the Nova Esperança Igarapé, one of the risk areas with inadequate housing, built nearby and on the bed of the stream. It is a case study, considering that there are similar situations in several places in the city. Locations considered by the Civil Defense to be unsuitable for housing. The objective is to understand the Public Housing Policies in Manaus, with the following specific objectives: Point out the Public Housing Policies in the city of Manaus; Identify residents in the vicinity of Igarapé Nova Esperança and whether they are included in housing programs; Describe the importance that Public Housing Policies represent for society. Manaus had an accelerated and disorderly growth, due to two periods of economic development: the Rubber Cycle with the export of Latex, and later with the implantation of industries in the Manaus Free Trade Zone, both presented great economic development, attracted immigrants from all locations in the world. However, the city did not have the structure to support an unexpected population growth. The consequences of poor economic and social distribution affect the low-income or no-income population, who seek an informal way to support their family and acquire a home. The government failed to develop Social Public Policies in the same proportion as population growth, resulting in disorderly urban growth. The methodology of the dissertation also covered the bibliographical and documental research, from the reading of primary sources and master's and doctoral research related to the theme, field research with semi-structured interviews through forms with families in situations of social and housing vulnerability, residents nearby or on the bed of the stream and the Nova Esperança neighborhood. Documentary data were collected at the State Superintendence of Housing in Amazonas – SUHAB and the Social and Environmental Program of the Igarapés de Manaus – PROSAMIM (state bodies), Vice-Presidency for Housing and Land Affairs – VPRESHAF and at the Municipal Urban Planning Institute – IMPLURB (Municipal bodies). After analyzing the data collected in the area of the stream, through interviews using forms, and discussions with several authors. The result presented was that the residents do not have the financial conditions to buy suitable property in another place, and that they are awaiting actions from the Public Housing Policies through the Social and Environmental Program of the Igarapés de Manaus - PROSAMIM, so that this population can be attended with suitable housing. However, according to the Special Projects Management Unit - UGPE, coordinator of PROSAMIM activities, there is no forecast of works for the Nova Esperança stream. Similar to the information in Organs SUHAB and VPRESHAF bodies, there are no applications for housing. The relevance of this research is to draw the public's attention to the dimension of the worsening of housing problems, with the intention that the State can continue to implement new housing projects over the next few years.
Keywords: Política habitacional - Brasil; Habitações - Manaus (AM); Habitação popular - Manaus (AM); CIENCIAS HUMANAS; Políticas públicas; Habitação; Igarapé/bairro; Nova Esperança - Manaus/AM